Role of echocardiography in reducing shock reversal time in pediatric septic shock: a randomized controlled trial - Ahmed A. EL‐Nawawy; Aly M. Abdelmohsen; Hadir M. Hassouna (Brazilian Society of Pediatrics, 2018)
Objective: To evaluate the role of echocardiography in reducing shock reversal time in pediatric septic shock. Methods: A prospective study conducted in the pediatric intensive care unit (PICU) of a tertiary care teaching hospital from September 2013 to May 2016. Ninety septic shock patients were randomized in a 1:1 ratio for comparing the serial echocardiography‐guided therapy in the study group with the standard therapy in the control group regarding clinical course, timely treatment, and outcomes. Results: Shock reversal was significantly higher in the study group (89% vs. 67%), with significantly reduced shock reversal time (3.3 vs. 4.5 days). PICU stay in the study group was significantly shorter (8 ± 3 vs. 14 ± 10 days). Mortality due to unresolved shock was significantly lower in the study group. Fluid overload was significantly lower in the study group (11% vs. 44%). In the study group, inotropes were used more frequently (89% vs. 67%) and initiated earlier (12[0.5-24] vs. 24[6-72] h) with lower maximum vasopressor inotrope score (120[30-325] vs. 170[80-395]), revealing predominant use of milrinone (62% vs. 22%). Conclusion: Serial echocardiography provided crucial data for early recognition of septic myocardial dysfunction and hypovolemia that was not apparent on clinical assessment, allowing a timely management and resulting in shock reversal time reduction among children with septic shock.